Primary amyloid tumour of the breast: a case report. Issue 8 (1st August 2002) - Deolekar, M V; Larsen, J; Morris, J A
Abstract : A case of primary amyloid tumour of the breast is reported with a brief review of the literature. The tumour was mammographically suspicious of carcinoma. Fine needle aspiration cytology yielded clumps of amorphous material surrounded by giant cells and lymphocytes. Subsequent histology showed nodular amyloid associated with osseous metaplasia and giant cell reaction. There are 13 cases of amyloid tumour of the breast reported in the literature and in four of these fine needle aspiration had been undertaken.